Genetic polymorphisms in CYP3A4 are associated with withdrawal symptoms and adverse reactions in methadone maintenance patients. (October 2011) - Chen, Chia-Hui; Wang, Sheng-Chang; Tsou, Hsiao-Hui; Ho, Ing-Kang; Tian, Jia-Ni; Yu, Cheng-Jou; Hsiao, Chin-Fu; Chou, Sun-Yuan; Lin, Yen-Feng; Fang, Kai-Chi; Huang, Chieh-Liang; Su, Lien-Wen; et al.
Aim: Methadone maintenance therapy is one of the standard treatments for heroin addiction. The isozyme CYP3A4 of the CYP system is one of the metabolic enzymes, as well as CYP2B6, responsible for the metabolism of methadone. The aim of the present study is to evaluate the potential use of genetic polymorphisms in CYP3A4 as biomarkers for the prediction of methadone treatment responses.Materials & methods: A total of 366 Han Chinese methadone maintenance treatment patients in Taiwan were recruited in this study. Main clinical assessments included the clinical opioid withdrawal scale (COWS), the treatment emergent symptom scale (TESS) and the plasma concentrations of methadone and its metabolites. Genetic associations of six SNPs in the CYP3A4 gene were calculated using a general linear model.Results: Genotypes and allele types of rs4646440 and rs2242480 were found to be significantly associated with the severity of withdrawal symptoms rated by COWS (p = 0.012, 0.0096, 0.017 and 0.012, respectively) as well as the side effects rated by TESS (p = 0.0089, 0.028, 0.0027 and 0.0085, respectively). The allele types associated with more severe withdrawal symptoms are also associated with more severe side effects and less betel nut ( Areca catechu ) use (p = 0.009 for rs4646440, p = 0.0063 for rs2242480). Further analyses on specific withdrawal symptoms in COWS showed that the genetic variants in rs4646440 are significantly associated with heart rate (allele type p = 0.0019).Conclusion: These results suggested that genetic variants in the CYP3A4 gene may be useful indicators for the severity of side effects and withdrawal symptoms for methadone treatment. Original submitted 2 May 2011; Revision submitted 8 July 2011